The Holocene evolution of the fluvial system of the southern Hessische Ried (Upper Rhine Graben, Germany) and its role for the use of the river Landgraben as a waterway during Roman times - Appel, Elena; Becker, Thomas; Wilken, Dennis; Fischer, Peter; Willershäuser, Timo; Obrocki, Lea; Schäfer, Henrik; Scholz, Markus; Bubenzer, Olaf; Mächtle, Bertil; Vött, Andreas (Quaternary science journal, 2024)
Intensive human intervention in the natural drainage system of the Hessische Ried (Upper Rhine Graben, Germany) resulted in the transformation of a large wetland into an intensively used cultural landscape. At least since the first century CE, when Romans conducted early river regulation and water management, the natural water network has experienced extensive anthropogenic re-organisation. The LandGraben project focuses on the reconstruction of the natural and anthropogenic watercourse systems along the river Landgraben, a tributary to the river Rhine in the northern Hessische Ried. Several rivers from the southern Hessische Ried could have fed the river Landgraben during Roman times via the meandering Palaeo-Neckar depression, thus increasing both length and discharge of the Roman waterway. - - In this study, we present results of our investigations within the southern Hessische Ried to reconstruct the former channel network that was used by Romans for the transportation of troops, wares and border security. Our approach integrates the use of high-resolution digital elevation models (DEMs) as a base for geophysical measurements (electrical resistivity tomography, ERT), direct push sensing and sediment coring in combination with sedimentological and geochemical analyses of the encountered sedimentary units. Local chronostratigraphies were established based on radiocarbon dating. - - Based on our results, we are able to differentiate a palimpsest of several abandoned fluvial channels throughout the southern Hessische Ried and to reconstruct the spatio-temporal development of the corresponding fluvial systems. Chronostratigraphic data show that the Palaeo-Neckar stopped flowing through the Hessische Ried around 10 000 cal BCE. Moreover, we found that the river Weschnitz, the largest of the possible Landgraben tributaries, stopped flowing through the Palaeo-Neckar depression at ca. 3000 cal BCE. Instead, it took a right-angled shortcut westwards to the river Rhine, north of the city of Lorsch. For the first time, we present geomorphological evidence that the river Weschnitz was not diverted by the Romans as speculated so far. This is corroborated by numerous wooden posts of human-made construction crossing an E-W running water course at the modern Weschnitz knee, with the oldest posts being dendrochronologically dated to the fourth and third millennia BCE. We further argue that the river Winkelbach/Lauter formed its knee towards the river Rhine and thus left the Palaeo-Neckar depression not later than the second century CE but most probably even contemporaneously with the formation of the Weschnitz diversion. In the case of the Winkelbach/Lauter, a high-energy flood event presumably related to strong rainfall and/or meltwater processes in the Odenwald Mountains is assumed to be responsible for the initiation of the new, diverted water course. With regard to the Landgraben and its use as a waterway within the Roman fluvioscape of the Hessische Ried, we therefore conclude that the Romans successfully collected water from several smaller rivers, such as from the rivers Modau and Darmbach and from even smaller tributaries, to make the river Landgraben a navigable waterway. The rivers Weschnitz and Winkelbach/Lauter, however, did not contribute any water to the Landgraben system during Roman times.
Gesehen am 16.06.2025